2022
DOI: 10.1021/acsomega.2c01075
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Cationic Nanoemulsion Ferrying Miconazole Nitrate with Synergism to Control Fungal Infections:In Vitro,Ex Vivo, andIn VivoEvaluations

Abstract: This study aimed to deliver a cationic nanoemulsion carrying miconazole nitrate (MCN) to control fungal infections using excipients for synergism. Peceol (oil) and labrasol (surfactant) were selected based on maximum solubility and zone of inhibition values against Candida albicans and Aspergillus niger . Optimized MCNE11 was evaluated [size, zeta potential, % entrapment efficiency (%EE), % transmittance, viscosity, refractive index, extrudability, polydispersity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…found that incorporating an amphoteric acyclovir into NE increased its solubility and caused a two-fold increase in its skin permeation when compared to the marketed gel [ 21 ]. Similar findings were made for a miconazole nitrate nanoemulsion, where the researchers discovered that encapsulating the miconazole nitrate within the oil globules of Peceol (oil phase) resulted in decreased haemolysis and toxicity, as well as improved permeability and solubility [ 22 ]. Drawing spur from the aforementioned research articles, authors of the current investigation have developed an oil-in-water (o/w) nanoemulsion loaded with AmB (AmB-NE) to tackle difficulties associated with conventional AmB therapy.…”
Section: Introductionsupporting
confidence: 55%
“…found that incorporating an amphoteric acyclovir into NE increased its solubility and caused a two-fold increase in its skin permeation when compared to the marketed gel [ 21 ]. Similar findings were made for a miconazole nitrate nanoemulsion, where the researchers discovered that encapsulating the miconazole nitrate within the oil globules of Peceol (oil phase) resulted in decreased haemolysis and toxicity, as well as improved permeability and solubility [ 22 ]. Drawing spur from the aforementioned research articles, authors of the current investigation have developed an oil-in-water (o/w) nanoemulsion loaded with AmB (AmB-NE) to tackle difficulties associated with conventional AmB therapy.…”
Section: Introductionsupporting
confidence: 55%
“…As mentioned before, we reported in vitro and in vivo behaviors of the MCZ-loaded nanoemulsion and cationic nanoemulsion after topical application onto rat skin and their permeation profile. It was required to develop and validate a HPLC method for the rat skin tissue to quantify the drug content and permeated drug concentration for the same formulations at high sensitivity, simplicity, and reproducibility. , These reported formulations were designated as MCNE11 (miconazole cationic nanoemulsion), MNE11 (miconazole nanoemulsion), MCZ-MKT (marketed gel), and MCZ-Sol (miconazole drug suspension). Nanoemulsions were composed of biocompatible lipid (peceol) and labrasol as a hydrophilic surfactant (hydrophilic lipophilic balance, HLB = 13.2).…”
Section: Methodsmentioning
confidence: 99%
“…Oleylamine served as a positive charge inducer and was expected to internalize with the negatively charged cellular surface of skin for maximized adhesion and subsequent drug permeation and drug penetration via electrostatic interactions. Other variables were kept constant to investigate the impact of positively charged nanoscale globular mediated enhanced permeation as discussed in the previous report . In the present study, it was required to develop an efficient, simple, and reproducible economic bioanalytical method for the quantitative estimation of MCZ from rat skin samples treated with MCNE11 and MNE11.…”
Section: Bionalytical Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations